Analisis Perbandingan Harga Saham dan Volume Transaksi Pada Perusahaan Telekomunikasi di Jakarta Islamic Index - Sa'diyah, Mahmudatus; Munzaroh, Sri Aqidah (Fakultas Syariah dan Ekonomi Islam Institut Pesantren Mathali'ul Falah, 2023)
Stock prices in the capital market are a reflection of all available information. Various events that occur in the capital market environment, both economic and non-economic, contain information that is used as a basis for decision making for investors so that they become one of the factors that determine the ups and downs of stock prices and transaction volume. This study aims to determine the value of a significant comparison between stock prices and transaction volumes before and after the national announcement of Covid-19 on telecommunication companies listed in JII (Jakarta Islamic Index). This research method uses quantitative methods in the form of comparative descriptive studies, the population of this study consists of 4 telecommunications companies listed in JII (Jakarta Islamic Index) using purposive sampling technique taken as many as 3 companies as samples. The data sample used is the closing of stock prices and transaction volume at 12 months (before covid-19) and at 12 months (after the announcement of covid-19) in the stock summary www.idx.co.id. The data of this study was processed using the Wilcoxon signed rank test, using SPSS 22. The results of this study prove that there is a significant comparison value between stock prices and transaction volumes before and after the national announcement of Covid-19 on telecommunication companies listed on the Jakarta Islamic Index ( JII).